2012 IEEE Consumer Communications and Networking Conference (CCNC) 2012
DOI: 10.1109/ccnc.2012.6181067
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of VoIP codecs over multi-rate EDCA

Abstract: Enhanced Distributed Channel Access (EDCA) is a mandatory part of the IEEE 802.11e standard which provides Medium Access Control (MAC) layer solution for Quality of Service (QoS) provisioning in Wireless Local Area Networks (WLANs). It is a contention based protocol which prioritizes channel access to QoS traffic using four Access Categories (ACs). In this paper, we introduce the performance evaluation of high priority Voice over Internet Protocol (VoIP) traffic over EDCA in multi-rate WLAN. In a multi-rate en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In case of EDCF, as there was a separate queue for each priority traffic, a minor change in throughput, latency and drop ratio was observed for voice as compared to DCF [6].The EDCA QoS mechanism produced significant improvements in the transmission of voice, which was consequential in the case of highly loaded network. Measurement results had shown that the use of QoS mechanisms reduced values of the mean and maximum delay, jitter and lost packets as compared to the case without QoS mechanism [7].When G711 VoIP connections is reduction in the bandwidth available for data traffic by approximately 900 Kbps [8].The MOS (mean opinion score) value of different VOIP CODECs (G.711) found was 4.48322 without background traffic (data) over 802.11e and 802.11b [9] Dynamic jitter buffer schemes give the highest user satisfaction in VoIP codec (G.711) and WLAN environments where compared without dynamic jitter buffer schemes [10].…”
Section: Related Workmentioning
confidence: 99%
“…In case of EDCF, as there was a separate queue for each priority traffic, a minor change in throughput, latency and drop ratio was observed for voice as compared to DCF [6].The EDCA QoS mechanism produced significant improvements in the transmission of voice, which was consequential in the case of highly loaded network. Measurement results had shown that the use of QoS mechanisms reduced values of the mean and maximum delay, jitter and lost packets as compared to the case without QoS mechanism [7].When G711 VoIP connections is reduction in the bandwidth available for data traffic by approximately 900 Kbps [8].The MOS (mean opinion score) value of different VOIP CODECs (G.711) found was 4.48322 without background traffic (data) over 802.11e and 802.11b [9] Dynamic jitter buffer schemes give the highest user satisfaction in VoIP codec (G.711) and WLAN environments where compared without dynamic jitter buffer schemes [10].…”
Section: Related Workmentioning
confidence: 99%